Women entrepreneurs in the era of metaverse: An Islamic economic perspective - Telsy Fratama Dewi Samad; Nugraha Hasan (Review of Islamic Social Finance and Entrepreneurship, 2022)
Purpose – This study aims to reveal the phenomenon of women entrepreneurs in the era of the Metaverse and analyze the Islamic economic viewpoint on using the Metaverse for business purposes. Methodology – For the research procedure, this study uses a qualitative method with descriptive analyses and collects the sources of research using the library research technique. Findings – This paper's findings showed that a growing number of entrepreneurs are conducting business in the Metaverse world, including women entrepreneurs. It also can be seen that cryptocurrencies used as tools for business transactions in the Metaverse are not in accordance with Islamic principles. It can be concluded that it is better for Muslim entrepreneurs to always be on track with the Islamic way, particularly in running their businesses.Implications – The rising amount of women entrepreneurs in this generation has become remarkable, concurrent with the evolution of digitalization which eases the praxis of business to occur, particularly in the era of the Metaverse. Yet, it is also essential to analyze the usage of the business platform in the sphere of Metaverse from the perspective of Islamic economics for business activity, not to contradict the principles of Islam. Originality – This study is to complete the lack of previous studies explaining the phenomenon of women entrepreneurs in the recent era of the Metaverse and discuss the perspective of Islamic economics concerning business in the Metaverse sphere.